Climate Change Awareness and Perceived Health Impacts: A Cross-Sectional Study among Nursing Students in Sindh, Pakistan - Ali, Nadir; Khowaja, Shaneela; Channar, Hussan Banno; Hussain, Mudasir; Soomro, Fatima; Dalpat, Jairam; Kumar, Suresh; Soomro, Farzana (Indus Journal of Bioscience Research, 2025)
Background: Climate change poses significant threats to global health, particularly in low- and middle-income countries. Nurses, as frontline healthcare providers, must be equipped with climate-health literacy to address climate-sensitive conditions. This study assessed the awareness and perceived health impacts of climate change among nursing students in Sindh, Pakistan. Methods: A cross-sectional survey was conducted over three months (from March – May of 2025) among 292 second-year Bachelor of Science in Nursing students from public and private colleges in Sindh. Participants were selected using cluster sampling. Data were collected through a validated self-administered questionnaire and analyzed using SPSS v27. Descriptive statistics summarized awareness levels, and chi-square tests examined associations between demographic variables and climate change awareness. Results: Most participants (91.4%) were familiar with the term “climate change” and 87.3% acknowledged its health impacts. Key causes identified included deforestation (66.4%) and air pollution (10.6%), while fewer recognized industrial emissions (1.7%). Respiratory diseases (82.5%), infectious diseases (80.8%), and malnutrition (68.2%) were commonly perceived health outcomes. Gender and age showed significant associations with awareness indicators (p<0.05). However, only 43.5% of students reported personal action against climate change, and 66.1% were unaware of governmental climate policies. Conclusion: Although nursing students demonstrated high general awareness of climate change, gaps in understanding specific causes, health impacts, and policies were evident. Integrating climate-health education into nursing curricula is critical for developing a climate-resilient healthcare workforce.